ผลการจัดกิจกรรมการเรียนรู้ที่ส่งเสริมทักษะการคิดวิเคราะห์ของนักเรียน ชั้นมัธยมศึกษาปีที่ 4 เรื่อง ภาคตัดกรวย ร่วมกับโปรแกรม GeoGebra - เขียวดี, ปพิชญา; เลิศอมรพงษ์, ชนิศวรา; จันทรา, ชานนท์ (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2020)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาทักษะการคิดวิเคราะห์ของนักเรียนชั้นมัธยมศึกษาปีที่ 4 เรื่อง ภาคตัดกรวย โดยใช้กิจกรรมการเรียนรู้ที่ส่งเสริมทักษะการคิดวิเคราะห์ร่วมกับโปรแกรม GeoGebra และ 2) ศึกษาแนวทางในการจัดกิจกรรมการเรียนรู้ที่ส่งเสริมทักษะการคิดวิเคราะห์ของนักเรียนชั้นมัธยมศึกษาปีที่ 4 เรื่อง ภาคตัดกรวย ร่วมกับโปรแกรม GeoGebra กลุ่มตัวอย่าง คือ นักเรียนชั้นมัธยมศึกษาปีที่ 4 โรงเรียนสตรีเศรษฐบุตรบำเพ็ญ ภาคเรียนที่ 2 ปีการศึกษา 2562 จำนวน 1 ห้องเรียน จำนวนนักเรียน 36 คน ซึ่งได้มาจากการสุ่มแบบกลุ่ม จากทั้งหมด 3 ห้องเรียน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลประกอบด้วย 1) แผนการจัดการเรียนรู้ เรื่อง ภาคตัดกรวย โดยใช้กิจกรรมการเรียนรู้ที่ส่งเสริมทักษะการคิดวิเคราะห์ร่วมกับโปรแกรม GeoGebra จำนวน 12 แผน และ 2) แบบวัดทักษะการคิดวิเคราะห์ เรื่อง ภาคตัดกรวย การวิเคราะห์ข้อมูลใช้การคำนวณค่าร้อยละ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน และ การทดสอบแบบ One-Simple T-Test เปรียบเทียบกับเกณฑ์ร้อยละ 60 ตามค่าเป้าหมายของโรงเรียนที่กำหนดไว้ ผลการวิจัยพบว่า 1) ทักษะการคิดวิเคราะห์ เรื่อง ภาคตัดกรวย สูงกว่าเกณฑ์ร้อยละ 60 อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และ 2) แนวทางในการจัดกิจกรรมการเรียนรู้ที่ส่งเสริมทักษะการคิดวิเคราะห์ของนักเรียนชั้นมัธยมศึกษาปีที่ 4 เรื่อง ภาคตัดกรวย ร่วมกับโปรแกรม GeoGebra มีแนวทางในการส่งเสริมทักษะการคิดวิเคราะห์ ดังนี้ 2.1) การจัดกิจกรรมการเรียนรู้ร่วมกับโปรแกรม GeoGebra ประกอบกับการใช้เทคนิคการถามตอบ โดยครูเป็นผู้ออกแบบกิจกรรมการเรียนรู้ที่มุ่งเน้นให้นักเรียนได้ลงมือปฏิบัติ สำรวจ ตรวจสอบและค้นพบข้อสรุปด้วยตนเอง การใช้เทคนิคการถามตอบ ตลอดการจัดกิจกรรมการเรียนรู้กระตุ้นให้นักเรียนคิดอย่างเป็นระบบ และ 2.2) การใช้กิจกรรมคู่และกิจกรรมกลุ่มสลับกัน ทำให้นักเรียนได้แลกเปลี่ยนความคิดเห็นซึ่งกันและกัน จากแนวทางที่กล่าวมาสามารถช่วยส่งเสริมทักษะการคิดวิเคราะห์ทั้งห้าทักษะให้กับนักเรียนได้ คำสำคัญ: ทักษะการคิดวิเคราะห์, โปรแกรม GeoGebra ABSTRACT The purposes of this research were 1) to study analytical thinking skills of Mathayomsuksa four students on Conic Sections by organizing learning activities in enhancing analytical thinking skills combine with GeoGebra and 2) to study guidelines for organizing learning activities in enhancing analytical thinking skills of Mathayomsuksa four students on Conic Sections combine with GeoGebra. The sample was Mathayomsuksa four students of one classroom, 36 students at Satreesethabuthbumpen School in the second semester of the academic year 2019 that was selected by cluster random sampling from three classrooms. The instruments in data collection consists of 1) 12 lesson plans of Conic Sections by organizing learning activities in enhancing analytical thinking skills combine with GeoGebra and 2) analytical thinking skills test of Conics Section and data analysis used percentage, mean and standard deviation by using the One-Simple T-Test and comparing it with the 60 percent of the school's target value. The results from the research found that 1) the analytical thinking skills on Conics Section higher than 60 percent criteria at the .05 level of significance and 2) the guidelines for organizing learning activities in enhancing analytical thinking skills of Mathayomsuksa four students on Conic Sections combine with GeoGebra, there are guidelines for organizing learning activities in enhancing analytical thinking skills as follows: 2.1) the organizing learning activities combine with GeoGebra and use of question and answer techniques by the teacher who are the designer of learning activities that focused on students to take action, explore, examine, and find conclusions on their own and also combine with the use of question and answer techniques throughout learning activities stimulate students with systematic thinking and 2.2) switching learning activities with couple activities and group activities led students exchange their opinions each other. As the approaches mentioned above, it can help in enhancing the analytical thinking skills for students. Keywords: Analytical Thinking Skills, GeoGebra